The Influence of Green Product, Green Marketing, and Green Brand Image Towards Green Purchase Intention on Sensatia Botanicals Products in Surabaya - Hotimah, Rena Arriva Dwi Nisaul Hotimah; Samsudin, Acep (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to investigate the influence of green product, green marketing, and green brand image on green purchase intention for Sensatia Botanicals products in Surabaya City. The variables used in this study are green product, green marketing, and green brand image as independent variables, and green purchase intention as the dependent variable. The research employs a quantitative method with data analysis using multiple linear regression analysis. The sample size for this study is 100 respondents, selected through nonprobability sampling using purposive sampling technique. Data collection is conducted through the use of questionnaires. The findings of this study suggest that the combination of green products, green marketing, and a green brand image all significantly and have a positive influence on green purchase intention for Sensatia Botanicals products. The green product variable, on a partial basis, exerts a positive and significant influence on green purchase intention forSensatia Botanicals products. Similarly, the green marketing variable, partially, exerts a positive and significant impact on green purchase intention for Sensatia Botanicals products.